Effect Of Short Term Aerobic Exercise (Football Training) On Lipid Profile And Myoglobin Levels In Apparently Healthy Students Of College Of Health Sciences, Nnamdi Azikiwe University, Nnewi Campus, Anambra State, Nigeria (International Journal of Scientific Research and Management (IJSRM), 2018)
This study investigated the effect of short term aerobic exercise on lipid profile and myoglobin levels in apparently healthy students of College of Health Sciences, Nnamdi Azikiwe University, Nnewi Campus, Anambra State, Nigeria. A total of 60 apparently healthy young students aged between 18-40 years were randomly selected for the study. They were rested for a period of two weeks after which they were subjected to football exercise for 30 minutes (3 times) in a week for a period of 3 weeks. The demographic and anthropometric data of subjects were obtained using a well-structured questionnaire. Their blood pressures reading were obtained also. Thereafter, 5mls of baseline (day 0) and post-exercise (day 21) blood samples were collected from each subject before the commencement and at the end of the exercise on the last day of the training into a plain container for estimation of biochemical parameters (TG, TC, LDL, HDL, Myoglobin levels) respectively using standard methods. Data obtained were statistically analysed by unpaired student t-test and Pearson r correlation. The result showed that the mean serum levels of TG (1.41±0.60 vs 1.04±0.43) TC (5.22±0.98 vs 4.41± 0.90), LDL (3.92±0.99 vs 3.36±0.92) as well as myoglobin (16.04± 4.64 vs 13.38±5.21) and DBP (75.16±10.54 vs 68.59±8.57) were significantly decreased, whereas, there was a significant increase in the mean serum level of HDL (0.83± 0.30 vs 0.95±0.28) and SBP (114.69±9.21 vs 131.48±12.84) in subjects after exercise when compared to before exercise (p<0.05). However, the mean BMI of the subjects remained the same before and after exercise (p>0.05). Therefore, short term moderate intensity aerobic exercise could be of importance in prevention and management of cardiovascular disease